Implementasi Google Sites Sebagai Media Pembelajaran Berbasis Web Untuk Meningkatkan Belajar Anak Berkebutuhan Khusus - Risqi Choirunnisa; Sri Widiyanti (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2023)
This research aims to implement Google Sites as a web-based learning media to improve the learning process of children with special needs. Children with special needs face unique learning challenges and need a tailored approach to help them reach their full potential. This study uses a qualitative approach using an action research design. A number of children with special needs from various backgrounds and ages were involved in this study. Data was collected through observation, in-depth interviews with classroom teachers, and children's responses to using Google Sites as a learning medium. The results of the study show that the implementation of Google Sites as a web-based learning media has the potential to improve the learning of children with special needs. Various features of this platform, such as the ability to present material with a variety of text, image, video media, flexibility of access, and ease of navigation, can facilitate learning that is more inclusive and interesting for children.